2023
DOI: 10.3390/cancers15092514
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane Protein Sortilin Is a Potential Biomarker and Target for Glioblastoma

Abstract: Glioblastoma (GBM) is a devastating brain cancer with no effective treatment, and there is an urgent need for developing innovative biomarkers as well as therapeutic targets for better management of the disease. The membrane protein sortilin has recently been shown to participate in tumor cell invasiveness in several cancers, but its involvement and clinical relevance in GBM is unclear. In the present study, we explored the expression of sortilin and its potential as a clinical biomarker and therapeutic target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…We further confirmed that sortilin is a promising drug target against T. gondii . Recent studies have shown that the sortilin inhibitor AF38469 effectively inhibits the invasion of pancreatic and brain cancers [ 31 , 32 ]. In the present study, AF38469 was found to inhibit T. gondii invasion and intracellular replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further confirmed that sortilin is a promising drug target against T. gondii . Recent studies have shown that the sortilin inhibitor AF38469 effectively inhibits the invasion of pancreatic and brain cancers [ 31 , 32 ]. In the present study, AF38469 was found to inhibit T. gondii invasion and intracellular replication.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular interaction experiments using bio-layer interferometry (BLI) technology confirmed that the Vps10, sortilin-C, and sortilin-M subdomains of sortilin were the binding regions of the transported proteins. The sortilin inhibitor AF38469, originally found to reduce the invasiveness of pancreatic cancer cells and glioblastoma cells [ 31 , 32 ], can also inhibit T. gondii cell invasion, replication in vitro, and infectivity in mice.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there have been no prior studies investigating the serum profiling of sortilin in patients with PTC. However, both sortilin and 8-OHdG measurements have been associated with more aggressive breast cancer ( 22 , 23 ), pancreatic cancer ( 24 , 25 ), liver cancer ( 26 , 27 ), and glioblastoma ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the properties of PGRN-related receptors and signalling pathways also poses promising research directions for further implementation in the therapy of brain tumours. The available data indicated that SORT1 is also highly upregulated within the cytoplasm and nuclei of gliomas obtained intraoperatively, where its expression level is positively correlated with the tumour grade [105,106]. Further studies also showed that SORT1 expression indicated a significantly poor prognosis, where 2-year survival rates for patients with high expression and low expression levels of SORT1 were 27% and 76%, and the 5-year survival rates of these patients were estimated to be 13% and 51%, respectively [107].…”
Section: Pgrn-related Receptors and Signalling Pathways In The Contex...mentioning
confidence: 98%